NeuralConstraints: integrating a neural generative model with constraint-based composition - Vassallo, Juan S.; Sandred, Örjan; Vincenot, Julien (Frontiers in Computer Science, 2025)
We present ‘NeuralConstraints,’ a suite of computer-assisted composition tools that integrates a feedforward neural network as a rule within a constraint-based composition framework. ‘NeuralConstraints’ combines the predictive generative abilities of neural networks trained on symbolic musical data with an advanced backtracking constraint algorithm. It provides a user-friendly interface for exploring symbolic neural generation, while offering a higher level of creative control compared to conventional neural generative processes, leveraged by the constraint solver. This article outlines the technical implementation of the core functionalities of ‘NeuralConstraints’ and illustrates their application through specific tests and examples of use.